2016
DOI: 10.18332/tpc/61546
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-led smoking cessation: The attitudes and practices of community pharmacists in Lagos state, Nigeria: A mixed methods survey

Abstract: IntroductIon Community pharmacists are well-positioned to support smoking cessation particularly in low and middle income countries. This study aims to assess the attitudes, barriers and pattern of pharmacist-led smoking cessation services and explore the factors associated with the willingness to offer smoking cessation services. Methods A cross-sectional descriptive study was carried out using qualitative and quantitative methods. Two hundred and forty two community pharmaceutical premises were randomly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…This study also identified the lack of materials for smoking services as a barrier to service provision, a result consistent with a related study conducted in Thailand by Thananithisak et al [ 10 ], and other studies [ 26 , 28 ]. This is despite that materials to aid smoking cessation could be requested without any charge from the Action on Smoking and Health Foundation Thailand (ASH Thailand).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study also identified the lack of materials for smoking services as a barrier to service provision, a result consistent with a related study conducted in Thailand by Thananithisak et al [ 10 ], and other studies [ 26 , 28 ]. This is despite that materials to aid smoking cessation could be requested without any charge from the Action on Smoking and Health Foundation Thailand (ASH Thailand).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with several other studies [ 10 , 18 , 20 , 21 , 25 , 26 , 27 ], this study found that lack of time was perceived to be a significant barrier to providing smoking cessation services. Interestingly, lack of time was more likely to be perceived as a barrier among those community pharmacists providing smoking cessation than those that did not.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, the roles of pharmacists in providing smoking cessation advice and services have been well-documented in the literature 18 . However, smoking cessation services are not a typical role of pharmacists in Nigeria, even though they have a positive attitude towards offering the service 21 .…”
Section: Introductionmentioning
confidence: 99%